Peningkatan Motivasi Belajar Peserta Didik : Pendekatan Reward dan Punishment di MTSN 4 Pasaman Barat - Rafika Juita; Puti Andam Dewi; Misrupita M (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Increasing student learning motivation using reward and punishment methods at MTsN 4 Pasaman Barat has been done well and implemented optimally by teachers. Therefore, this research describes increasing learning motivation through reward and punishment methods at MTsN 4 West Pasaman. The study focused on the reward and punishment system implemented by teachers. This research uses a descriptive qualitative approach. In obtaining data, researchers used interview, observation and documentation methods. The results of this research conclude that: 1) the rewards used are in the form of praise, applause and gifts, while the punishments applied are in the form of reprimands and non-verbal communication that is not negative, 2) rewards and punishment can increase student learning motivation at MTsN 4 Pasaman Barat thus influences student learning outcomes, 3) Rewards and Punishments make students active in learning so that learning takes place effectively.